Female labor migration and the restructuring of migration discourse: a study of female workers from Chitwan, Nepal - Kharel, Arjun (Kansas State University, 2016)
Nepali women are often barred from going abroad through discriminatory state policies, and the women engaging in foreign employment are generally perceived as "loose" women in Nepalese society. The female migrant workers are also represented as lacking "agency" and "victims" of sex trafficking in the Nepalese media. Despite the unfavorable socio-political contexts, a substantial number of Nepali women have engaged in transnational labor migration in the last two decades, often "illegally" by using the open Nepal-India border to reach the destination countries. The study investigates the impact of women's migration on the dominant discourse relating to female workers' sexuality and agency by analyzing the experiences of female workers from Chitwan, Nepal, who have returned after working as housemaids in the Persian Gulf. The study finds that the dominant discourse is both contested and reproduced during the emigration process and after the return of female workers. However, the dominant discourse is overall restructured in the emigrant communities due to women's participation in foreign employment and return with diverse experiences. As women's varied migration experiences are hardly reported in the national media, the discursive change in the local communities does not necessarily bring a (similar) change in the national discourse. While violence prevailed against female workers in the Gulf, most acts of violence were indirect and non-physical. The extreme forms of violence, such as physical and sexual abuses, which are usually reported in the media, were somewhat uncommon. The major complaints of the respondents were low wages, withholding and non-payment of wages, withholding of passport, extremely long hours of work, constant criticism, lack of adequate rest, and the feeling of confinement. The violence against the housemaids was largely facilitated by the sponsorship-based labor recruitment system in the Gulf that bound the migrant workers with their employers. At the micro level, the living arrangement (having to live with the employers) was also a contributing factor to violence against the female workers. The female workers who were employed in a household with multiple housemaids were less likely to experience violence than those who were the only maid in the employer's house.
Keywords: Migration; Female Migration; Nepal; Discourse; Housemaids; Gulf